5′ UTR variants in the quantitative trait gene Hnrnph1 support reduced 5′ UTR usage and hnRNP H protein as a molecular mechanism underlying reduced methamphetamine sensitivity. Issue 7 (13th May 2020) - Ruan, Qiu T.; Yazdani, Neema; Reed, Eric R.; Beierle, Jacob A.; Peterson, Lucy P.; Luttik, Kimberly P.; Szumlinski, Karen K.; Johnson, William E.; Ash, Peter E.A.; Wolozin, Benjamin; Bryant, Camron D.
Abstract: We previously identified a 210 kb region on chromosome 11 (50.37‐50.58 Mb, mm10) containing two protein‐coding genes ( Hnrnph1, Rufy1 ) that was necessary for reduced methamphetamine‐induced locomotor activity in C57BL/6J congenic mice harboring DBA/2J polymorphisms. Gene editing of a small deletion in the first coding exon supported Hnrnph1 as a quantitative trait gene. We have since shown that Hnrnph1 mutants also exhibit reduced methamphetamine‐induced reward, reinforcement, and dopamine release. However, the quantitative trait variants (QTVs) that modulate Hnrnph1 function at the molecular level are not known. Nine single nucleotide polymorphisms and seven indels distinguish C57BL/6J from DBA/2J within Hnrnph1, including four variants within the 5′ untranslated region (UTR). Here, we show that a 114 kb introgressed region containing Hnrnph1 and Rufy1 was sufficient to cause a decrease in MA‐induced locomotor activity. Gene‐level transcriptome analysis of striatal tissue from 114 kb congenics vs Hnrnph1 mutants identified a nearly perfect correlation of fold‐change in expression for those differentially expressed genes that were common to both mouse lines, indicating functionally similar effects on the transcriptome and behavior. Exon‐level analysis (including noncoding exons) revealed decreased 5′ UTR usage of Hnrnph1 and immunoblot analysis identified a corresponding decrease in hnRNP H protein in 114 kb congenic mice. Molecular cloning of the Hnrnph1 5′ UTR containing all four variants (but none of them individually) upstream of a reporter induced a decrease in reporter signal in both HEK293 and N2a cells, thus, identifying a set of QTVs underlying molecular regulation of Hnrnph1 .